Effect of abdominal massage combined with moxibustion in the treatment of Qi-deficiency type chronicfunctional constipation in elderly people (腹部推拿联合艾灸治疗气虚型老年慢性功能性便秘效果观察) - YU Fei (于飞); WANG Xu (王旭); ZHANG Shufen (张淑芬); CHEN Qing (陈晴); GUO Jinyu (郭金雨) (Association of Integrative Nursing, 2024)
Objective To observe the effect of abdominal massage combined with moxibustion in the treatment of Qi-deficiency type chronic functional constipation in elderly people. Methods Totally 100 elderly patients with chronic functional constipation of Qi-deficiency type were randomly divvied into the control group and observation group, with 50 cases in each group. The control group received routine treatment and abdominal massage, and the observation group received abdominal massage combined with moxibustion. The defecation condtion, Tradition Chinese Medicine syndrome score and clinical curative effect were compared between two groups. Results The Patient Assessment of Constipation Symptoms(PAC-SYM) score was decreased in both two groups after intervention (P＜0. 05), and PAC-SYM score in the observation group was lower than that in the control group (P＜0. 05). The Tradition Chinese Medicine syndrome score was decreased in both two groups after intervention (P＜0. 05), and Tradition Chinese Medicine syndrome score in the observation group was lower than that in the control group (P＜0. 05). The total effective rate was 94. 00%(47/50) in the observaiton group, which was higher than 76. 00%(38/50) in the control group (P＜0. 05). Conclusion The abdominal massage combined with moxibustion is effective to relieve the clinical symptoms of Qi-deficiency type chronic functional constipation in elderly people. (目的 观察腹部推拿联合艾灸治疗气虚型老年慢性功能性便秘的效果。方法 选取2022年4月-2023年12月在医院住院治疗的气虚型老年慢性功能性便秘患者100例为研究对象, 采用随机数字表法分为对照组和观察组, 各50例。对照组给予常规治疗和腹部推拿, 观察组在对照组基础上联合艾灸治疗。治疗7 d后比较两组患者排便情况、中医证候积分及临床疗效。结果 治疗后两组便秘患者症状自评量表(PAC-SYM)评分均较治疗前降低(P＜0. 05), 且观察组治疗后评分低于对照组(P＜0. 05)。治疗后两组排便无力、腹中隐痛、食欲不振、乏力懒言等中医证候积分均较治疗前降低(P＜0. 05), 且观察组治疗后评分低于对照组(P＜0. 05)。观察组总有效率为94. 00%(47/50), 高于对照组的76. 00%(38/50), 差异有统计学意义(P＜0. 05)。结论 腹部推拿联合艾灸治疗可有效缓解气虚型老年慢性功能性便秘患者的临床症状。)